Sensitization to occupational allergens in hairdressing apprentices diagnosed already before entering vocational training - Aleksandra Golińska-Zach; Patrycja Krawczyk-Szulc; Marta Wiszniewska; Ewa Nowakowska-Świrta; Dominika Świerczyńska-Machura; Diana Tymoszuk; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2016)
Background: Hairdressers are occupationally exposed to many allergenic and irritating substances. Additionally, hairdressing apprentices are exposed to the same allergens as professional hairdressers, due to the fact that vocational training starts in the beginning of the education. This study was undertaken to investigate early occurrence of sensitization to occupational allergens in hairdressing apprentices before the onset of the vocational training. Material and Methods: Three hundred and seven hairdressing apprentices were assessed using a questionnaire and skin prick tests (SPTs) to common and occupational allergens. The level of total and serum specific immunoglobulin E (IgE) to occupational allergens was evaluated and spirometry was performed. Results: At least one skin and/or respiratory and/or conjunctival symptom was reported by 29.9% of subjects. Among subjects with at least one symptom, 28.2% of them were atopic whereas among 43.4% of them total IgE level was elevated. Atopy was found in 20% cases. In the case of one apprentice, positive SPT for paraphenylenediamine was found. Nearly 33% of apprentices had elevated total IgE level and 5 of them had specific IgE for occupational allergens. Conclusions: The study revealed that hairdressing apprentices might be sensitized to occupational allergens even before the beginning of vocational training, due to prior non-professional exposure to hairdressing agents. Furthermore, many of them report skin, respiratory and conjunctival symptoms, often connected with chronic disease diagnosis. Thus, candidates for hairdressers should be examined thoroughly before the start of the education and tests for allergy to hairdressing substances are indicated. Med Pr 2016;67(5):567-575